Analogous modulation of inflammatory responses by the endocannabinoid system in periodontal ligament cells and microglia - Andreas Jäger; Maria Setiawan; Eva Beins; Ingo Schmidt-Wolf; Anna Konermann (Head & Face Medicine, 2020)
Abstract Background Periodontal ligament (PDL) cells initiate local immune responses, similar to microglia regulating primary host defense mechanisms in neuroinflammatory events of the central nervous system. As these two cell types manifest similarities in their immunomodulatory behavior, this study investigated the thesis that the immunological features of PDL cells might be modulated by the endocannabinoid system, as seen for microglia. Methods A human PDL cell line and an Embryonic stem cell-derived microglia (ESdM) cell line were grown in n = 6 experimental groups each, incubated with cannabinoid receptor agonists arachidonoylethanolamine (AEA) (50 μM) or Palmitoylethanolamide (PEA) (50 μM) and challenged with centrifugation-induced inflammation (CII) for 6 and 10 h. Untreated samples served as controls. Quantitative real-time polymerase chain reaction was applied for gene expression analyses of inflammatory cytokines, cannabinoid receptors and ionized calcium binding adaptor molecule 1 (IBA-1). Microglia marker gene IBA-1 was additionally verified on protein level in PDL cells via immunocytochemistry. Proliferation was determined with a colorimetric assay (WST-1 based). Statistical significance was set at p < 0.05. Results IBA-1 was inherently expressed in PDL cells both at the transcriptional and protein level. AEA counteracted pathological changes in cell morphology of PDL cells and microglia caused by CII, and PEA contrarily enhanced them. On transcriptional level, AEA significantly downregulated inflammation in CII specimens more than 100-fold, while PEA accessorily upregulated them. CII reduced cell proliferation in a time-dependent manner, synergistically reinforced by PEA decreasing cell numbers to 0.05-fold in PDL cells and 0.025-fold in microglia compared to controls. Conclusion PDL cells and microglia exhibit similar features in CII with host-protective effects for AEA through dampening inflammation and preserving cellular integrity. In both cell types, PEA exacerbated proinflammatory effects. Thus, the endocannabinoid system might be a promising target in the regulation of periodontal host response.